2023
DOI: 10.3389/fphar.2022.1009025
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visualized analysis of sodium–Glucose cotransporter 2 inhibitors

Abstract: Background: Sodium—glucose cotransporter 2 inhibitors have proved to be extremely effective and reliable in reducing hyperglycemia, and have also been used for the treatment of cardiovascular and renal disease in patients with or without type 2 diabetes. Thousands of research articles on SGLT2 inhibitors have been published in the past, but few bibliometric analyses have systematically been studied this field. We aimed to visualize the global research hotspots and trends of SGLT2 inhibitors using a bibliometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…EMPA protected the heart from inflammation and energy depletion by activating AMPK [53], and CANA exhibited anti-inflammatory and anti-apoptotic effects in the human myocardium through AMPK activation [22]. Bibliometric and visual analysis suggested that further research in the future regarding SGLT2is would primarily investigate their molecular mechanisms, especially their specific interconnection with AMPK [54]. Previous experimental results indicated that AMPK activation by SGLT2is inhibits the proliferation of various cancer cells [42,55].…”
Section: Discussionmentioning
confidence: 99%
“…EMPA protected the heart from inflammation and energy depletion by activating AMPK [53], and CANA exhibited anti-inflammatory and anti-apoptotic effects in the human myocardium through AMPK activation [22]. Bibliometric and visual analysis suggested that further research in the future regarding SGLT2is would primarily investigate their molecular mechanisms, especially their specific interconnection with AMPK [54]. Previous experimental results indicated that AMPK activation by SGLT2is inhibits the proliferation of various cancer cells [42,55].…”
Section: Discussionmentioning
confidence: 99%